(untitled) (Contemporary Central & East European Law, 2024)
The subject of analysis in this article is Professor Stanisław Kasznica’s reflections on public administration. His postulates concerning the functioning of public administration with the criteria of “good administration” are compared with the current understanding of the matter. The main intention is thus to demonstrate the validity of the theses put forward by the professor. In conclusion, it can be stated that the main thesis of the article has been confirmed, that most of the assumptions in the relationship between the administration and the individual were previously known and inspired the postulates raised by contemporary authors. These demands were a harbinger of the adoption in the EU of one of the fundamental rights of the EU – the right to good administration.